Authentication of a survival nomogram for non-invasive micropapillary breast cancer - Zhang, Mingkun; Qin, Yuan; Hou, Niuniu; Ji, Fuqing; Zhang, Zhihao; Zhang, Juliang (Frontiers in Oncology, 2023)
We aimed at establishing a nomogram to accurately forecastpredict the overall survival (OS) of non-metastatic invasive micropapillary breast carcinoma (IMPC). Methods: In the training cohort, data from 429 patients with nonmetastatic IMPC were obtained through the Surveillance, Epidemiology, and End Results (SEER) database. Other 102 patients were enrolled at the Xijing Hospital as validation cohort. Independent risk factors affecting OS were ascertained using univariate and multivariate Cox regression. A nomogram was established to forecastpredict OS at 3, 5 and 8 years. The concordance index (C-index), the area under a receiver operating characteristic (ROC) curve and calibration curves were utilized to assess calibration, discrimination and predictive accuracy. Finally, the nomogram was utilized to stratify the risk. The OS between groups was compared through Kaplan-Meier survival curves. Results: The multivariate analyses revealed that race (p = 0.047), surgery (p = 0.003), positive lymph nodes (p = 0.027), T stage (p = 0.045) and estrogen receptors (p = 0.019) were independent prognostic risk factors. The C-index was 0.766 (95% CI, 0.682-0.850) in the training cohort and 0.694 (95% CI, 0.527-0.861) in the validation cohort. Furthermore, the